Effects of income and residential area on survival of patients with head and neck cancers following radiotherapy: working age individuals in Taiwan - Yu Cheng Lai; Pei Ling Tang; Chi Hsiang Chu; Tsu Jen Kuo (PeerJ, 2018)
Objectives The five-year survival rate of head and neck cancer (HNC) after radiotherapy (RT) varies widely from 35% to 89%. Many studies have addressed the effect of socioeconomic status and urban dwelling on the survival of HNC, but a limited number of studies have focused on the survival rate of HNC patients after RT. Materials and methods During the period of 2000–2013, 40,985 working age individuals (20 < age < 65 years) with HNC patients treated with RT were included in this study from a registry of patients with catastrophic illnesses maintained by the Taiwan National Health Insurance Research Database (NHIRD). Results The cumulative survival rate of HNC following RT in Taiwan was 53.2% (mean follow-up period, 3.75 ± 3.31 years). The combined effects of income and geographic effect on cumulative survival rates were as follows: high income group > medium income group > low income group and northern > central > southern > eastern Taiwan. Patients with moderate income levels had a 36.9% higher risk of mortality as compared with patients with high income levels (hazard ratio (HR) = 1.369; p < 0.001). Patients with low income levels had a 51.4% greater risk of mortality than patients with high income levels (HR = 1.514, p < 0.001). Conclusion In Taiwan, income and residential area significantly affected the survival rate of HNC patients receiving RT. The highest income level group had the best survival rate, regardless of the geographic area. The difference in survival between the low and high income groups was still pronounced in more deprived areas.